Along the Little Spokane (River) : a sense of place - Brown, Ty A. (Little Spokane Bookworks, 2024)
The Little Spokane River -- A sense of place offers a captivating journey through the rich history and natural beauty of the Little Spokane River valley. Nestled north of the city of Spokane, this region is known for its stunning natural features -- rolling hills, lush forests, and the winding water of the Little Spokane River, once home to thriving salmon and trout fisheries. The book explores the valley's deep cultural roots, from Native American life centered around the river's resources to the rise of dairy farming, timber, railroads, and mills that shaped the local economy. Through vivid storytelling and historical accounts, readers learn about the transformation of the landscape and the enduring community efforts to conserve the valley's pristine environment. As the region faces future challenges, The Little Spokane River -- A sense of Place emphasizes the importance of balancing growth with a deep respect for the natural and cultural heritage of this remarkable valley.